Engaging Students : The Next Level of Working on the Work - Schlechty, Phillip C., 1937- (San Francisco : Jossey-Bass, 2011)
'Working on the Work (WOW) offers a motivational framework for improving student performance by improving the quality of school designed for students. In this second edition, author Phillip Schlechty incorporates what he's learned from the field and from the hundreds of workshops he and his organization, the Schlechty Center, have conducted since the book's first publication. WOW is a theory of motivation that tries to answer the question:'What can teachers build into the task and activities they design for students that will increase the prospect which students will find meaning in the tasks assigned?' The guide is filled with practical wisdom'--
Includes bibliographical references (pages 197-198) and index.
Keywords: School improvement programs -- United States; Academic achievement -- United States; Curriculum change -- United States; School environment -- United States